Criminal types of crimes of violence domestic violence - Bazantes Escobar, Washington Javier; Gaibor-Becerra, Angélica María; Ballesteros Jiménez, Rocío De Las Mercedes (Revista Universidad de Guayaquil, 2018)
The criminal types describe the criminal conducts established in the penal law and in the case of the crimes of intrafamily violence, the comparative legislation consecrates in clear form of those who conform or are members of the family nucleus; more than the legal right violated in domestic violence crimes is family harmony and peace and the legal right affected by physical abuse is the personal integrity of the victim, aspects that envisage dissimilar procedural situations, it is not the same to file a criminal action for intrafamily violence and another for injuries. In the Ecuadorian case, moreover, there is an overreaching of the criminal type, the criminal actions for intrafamily violence and injuries are intermingled, it being conceived that the fight against intrafamily violence is inexorably reducing the prisoner to prison as the prison solves everything, remember that the Criminal law is of last ratio. To this it is added that the expartners, in spite of having broken the marital lasso, courtship, de facto union, relationship of affectivity or intimacy, maintain the status of member of the family nucleus forever and in case of physical or other aggression they are submitted to the intrafamily violence process and not for injuries.